Inisiatif Super Student: Meningkatkan Motivasi Belajar Siswa MA melalui Seminar - Nisa’, Chintya Hilyatun; Puspitasari, Kholil; Masnida, Masnida (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to analyze the extent to which the specially designed Super Student seminar can increase student learning motivation compared to conventional learning methods. The object of service regarding increasing learning motivation through the Super Student Initiative seminar is located at Madrasah Aliyah (MA) Darul Magfur Blumbangan Banyuwangi. The design in this service uses a service method with the type of CBPR (Community Based Participatory Research). The stages in this service include Laying the foundation, Research Planning, Information Gathering and Analysis and Acting on findings. The result of this service is that the super studen seminar succeeded in increasing learning motivation through the Learning Plan method, Impact of Storytelling, and Increased Career Aspirations. In conclusion, the Super Student seminar plays an important role in increasing student learning motivation through a deeper personal approach, so that it can have a positive impact on student academic achievement. This service supports the implementation of seminars as an effective method to increase learning motivation in other schools.